Moxibustion for stable chronic obstructive pulmonary disease: A protocol for systematic review and meta-analysis - Wang, Yanping (Medicine (Baltimore), 2021)
BACKGROUND: There is no optimal treatment to alleviate the decline of lung function in the stable phase of chronic obstructive pulmonary disease (COPD). The effectiveness of moxibustion as an adjunctive treatment for COPD in the stable phase has been reported clinically, but the conclusions on efficacy and safety have not been unified. This study will systematically evaluate the efficacy and safety of moxibustion on the treatment of COPD in the stable phase, providing clinical-based evidence METHODS: We will systematically search 7 literature databases and 2 clinical trial registration platforms. The searching time will be conducted from the establishment of databases to March 31, 2021, regardless of language. We will include the randomized controlled trial (RCT) evaluation of moxibustion combined with basic therapy vs basic therapy alone for the treatment of stable COPD. We will assess the risk of bias for individual RCTs using the Cochrane Handbook 5.1.0 evaluation tool. The primary outcome is forced expiratory volume in 1 second/forced vital capacity. The secondary outcomes include forced expiratory volume in 1 second, forced vital capacity, six-minute walking distance, COPD assessment test score, maximum ventilation, response to treatment, and incidence of adverse events. We will collect the effective data of individual RCT through systematic analysis of the random effect model. Heterogeneity will be tested by Cochran Q test and I-squared statistics. Two subgroup analyses will be performed to explore the sources of heterogeneity based on clinical experience. Excluding RCTs with a high risk of bias, fixed-effect model will be used for sensitivity analysis to test the robustness of the meta-analysis results. The publication bias will be assessed by funnel plot and Egger test. RESULTS: This study will provide systematic evidence on the efficacy and safety of moxibustion on the treatment of patients with stable COPD through strict quality assessment and reasonable data synthesis. We hope that the results will be submitted to a peer-reviewed journal for publication. CONCLUSION: This systematic review will provide the best current evidence for the adjuvant treatment of stable COPD with moxibustion. INPLASY REGISTRATION NUMBER: INPLASY202140047.